Development of lung metastases in mouse models of tongue squamous cell carcinoma. (20th August 2020) - Marcazzan, Sabrina; Dadbin, Ali; Brachi, Giulia; Blanco, Elvin; Varoni, Elena Maria; Lodi, Giovanni; Ferrari, Mauro
Abstract: Objective: Oral squamous cell carcinoma (OSCC) represents 3%–4% of all cancers. Despite the increasing incidence of OSCC distant metastasis and poor prognosis, few animal models of OSCC distant metastasis have been reported. In this study, we established mouse models of OSCC lung metastasis by orthotopic and tail vein injection of new OSCC cell lines. Methods: For the tail vein model, we used a novel cell line isolated from lung metastases reproduced in vivo after intravenous injection of HSC‐3 GFP/luciferase cells and sorted for GFP expression (HSC‐3 M1 GFP/luciferase). Lung metastases were assessed by imaging techniques and further confirmed by histology. For the orthotopic model, HSC‐3 GFP/luciferase cells were injected into the tongue of athymic nude mice. The primary tumor and metastases were assessed by in vivo imaging, histology, and immunohistochemistry. Results: The orthotopic model presented spontaneous lung metastases in 50% of the animals and lymph node metastases were present in 83% of cases. In the tail vein model, a lung metastasis rate of 60% was observed. Conclusions: Lung metastases were successfully reproduced by orthotopic and tail vein injection. Since lymph node metastases were present, the orthotopic model with HSC‐3 GFP/luciferase cells may be suitable to investigate metastatic dissemination in OSCC.